SISTEM INFORMASI MANAGEMEN COMPLAIN SERVICE CENTER DALAM MENINGKATKAN PELAYANAN TERHADAP CUSTOMER BERBASIS CRM DI GALLERY SMARTFREN KUNINGAN (Studi Kasus : Gallery Smartfren Kuningan) - Meri Siti Maryam (NUANSA INFORMATIKA, 2018)
The business world of the industry continues to grow to be part of one of the spearheads of telecommunication companies in an effort to realize the consumer market. Everyone present at the Kuningan Smartfren Gallery often happens to everyone who comes to the gallery to find people who want to access the hard service, in this case often in the gallery traversed by consumers who should be handled well by the smartfren while the number of waiters limited. The answer is that consumers often do complain to the party smartfren dikarnakan service dissatisfaction. To avoid these things then the management system will provide more effective complaints for every consumer who can access properly and on time. One form of method used to discuss the problem is the CRM method or known as Customer Relations Management. One of the implementation of CRM that fall into this category is in the form of sms gateway.Keywords: Customer Relationship Management Method, SMS GATEWAY